Standardization of orthographic variability of Tuvan toponyms - Igor А. Dambuev (Novye issledovaniâ Tuvy, 2018)
The paper deals with the spelling variations of the official Tuvan toponymy and the unification of it in Russian language on the materials of the State Catalogue of Geographical Names, topographical maps and legislative acts. The unification of geographical names is a matter of national importance and a subject of Russian legislation. According to Russian legislation, geographical names are considered a constituent part of historical and cultural heritage of the peoples of the Russian Federation. In recent decades the UN Conferences on the Standardization of the Geographical Names has been recommending using the geographical names of ethnic minorities and indigenous people to preserve and promote their culture. The paper examines several types of spelling variations common for Tuvan toponymy, such as rendering Tuvan long vowels in Russian language, the letter ы after hushing sounds, yotized vowels, voiceless and voiced consonants, and hyphenated and joined-up spelling of place names. The Guidelines for rendering of Tuvan geographical names on maps (1964) did not intend to render the length of Tuvan vowels, while the Guidelines for Russian rendering of Tuvan geographical names (1975) and the Code of Rules for Russian rendering of Tuvan geographical names (2015) provide rules on rendering the length of vowels by duplication of corresponding letters to avoid false homonymy of Tuvan toponyms. The same is true for the rendering of the letter ы after hushing letters ш, ч, ж, which replaced in this position the letter и as recommended by the Guideline of 1964. The unification of rendering of yotized vowels followed the principle of similarity between Russian rendering and original spelling. The variations of voiceless and voiced consonants in Russian rendering are occasioned not only by the adaptation of Tuvan toponyms in Russian but also by peculiarities of Tuvan consonant system. The variations of hyphenated and joined-up spelling of Tuvan toponyms in Russian are caused by differences between Russian rendering of compound toponyms Tuvan and other Turkic languages. In diachronic aspect during the unification of Tuvan toponyms in Russian the initial commitment to Russian spelling rules gave place to the trend of rendering of particularities of the Tuvan language. In the author’s point of view, this trend promotes preservation of Tuvan toponymy as a cultural and historical heritage. At the same time, revisions in the rules of Russian rendering of Tuvan toponyms led to toponymical variability, which means that the same Tuvan toponyms can be rendered in Russian in different ways. This fact impedes the unification of Tuvan toponyms both in Tuvan and Russian.